La guerra civil española : 50 años después - Tuñon de Lara, Manuel, 1915-1997; Arostegui, Julio; Cardona, Gabriel; Viñas, Angel (Barcelona : Labor, 1985)
Overzichtswerk van de eerste 50 jaar Franco-bewind na de Spaanse burgeroorlog.